Clinical Significance of Pituitary Tumor Transforming Gene 1 and Transgelin-2 in Pancreatic Cancer. (January 2013) - Lin, H.; Chen, Q-L.; Wang, X-Y.; Han, W.; He, T-Y.; Yan, D.; Chen, K.; Su, L-D.
Human pituitary tumor transforming gene 1 (PTTG1) is an oncogenic transcription factor that is overexpressed in many malignancies, especially cancers with metastatic potential, while transgelin-2 (TAGLN2) is an actin-binding protein shown to be a tumor suppressor. However, the expression and clinical significance of PTTG1 and TAGLN2 in pancreatic cancer remain unclear. The present study aimed to investigate the expression and clinical significance of PTTG1 and TAGLN2 in human primary pancreatic cancer. Seventy-five cases of human pancreatic cancer tissues were collected. The expression of PTTG1 and TAGLN2 protein was assessed using immunohistochemistry (IHC) through tissue microarray procedure. The clinicopathologic characteristics of all patients were analyzed. As a result, the expression of PTTG1 and TAGLN2 in cancerous tissues showed the positive staining mainly in the cytoplasm, and they were found in cancerous tissues with higher strong reactivity rate compared with the adjacent non-cancer tissues (ANCT) (56.0% vs 22.7%, P <0.001; 100% vs 84%, P =0.002), elevating with the ascending order of tumor malignancy. Furthermore, the positive expression of PTTG1 was associated with the gender of pancreatic cancer patients, but did not correlate with their age, pathological styles, tumor size, tumor sites, TNM staging, perineural infiltration and distant metastasis (each P >0.05). In addition, Spearman rank correlation analysis showed the positive correlation of PTTG1 with TAGLN2 (r=0.624, P <0.001). Taken together, PTTG1 and TAGLN2 are highly expressed in human pancreatic cancer, and the positive expression of PTTG1 is associated with the gender of cancer patients, suggesting that it may represent a potential therapeutic target for the treatment of pancreatic cancer.